Ocular Adverse Effects of Intravitreal Bevacizumab Are Potentiated by Intermittent Hypoxia in a Rat Model of Oxygen-Induced Retinopathy - Jeffrey J. Tan; Charles L. Cai; Eric M. Shrier; Lois McNally; Douglas R. Lazzaro; Jacob V. Aranda; Kay D. Beharry (Journal of Ophthalmology)
Intravitreal bevacizumab (Avastin) use in preterm infants with retinopathy of prematurity is associated with severe neurological disabilities, suggesting vascular leakage. We examined the hypothesis that intermittent hypoxia (IH) potentiates intravitreal Avastin leakage. Neonatal rats at birth were exposed to IH from birth (P0)–P14. At P14, the time of eye opening in rats, a single dose of Avastin (0.125 mg) was injected intravitreally into the left eye. Animals were placed in room air (RA) until P23 or P45 for recovery (IHR). Hyperoxia-exposed and RA littermates served as oxygen controls, and equivalent volume saline served as the placebo controls. At P23 and P45 ocular angiogenesis, retinal pathology and ocular and systemic biomarkers of angiogenesis were examined. Retinal flatmounts showed poor peripheral vascularization in Avastin-treated and fellow eyes at P23, with numerous punctate hemorrhages and dilated, tortuous vessels with anastomoses at P45 in the rats exposed to IH. These adverse effects were associated with robust increases in systemic VEGF and in both treated and untreated fellow eyes. Histological analysis showed severe damage in the inner plexiform and inner nuclear layers. Exposure of IH/IHR-induced injured retinal microvasculature to anti-VEGF substances can result in vascular leakage and adverse effects in the developing neonate.